(untitled) (Research, Society and Development, 2022)
Education in the context of health promotion and recovery and disease prevention is an important practice and contributes to deaf patients’ understanding of their health-disease-care process. The objective of this review is to identify inclusion experiences involving people with deafness in the scope of pharmaceutical services practices. For development, it was considered to analyze the indexed publications of five databases, LILACS, Web of Science, Scopus, Embase and Pubmed. The combinations of descriptors were constituted by the Boolean operators AND and OR: ((Deaf OR Deafness OR “Hearing loss” [All Fields]) AND (Pharmaceutical Services [All Fields] OR Pharmaceutical Care [All Fields])) and ((Deaf) OR Deafness OR “Hearing loss” [All Fields]) AND (“Pharmaceutical Services” [All Fields] OR “Pharmaceutical Care” [All Fields])). Articles in English, Portuguese and Spanish were analyzed, from January 2011 to September 2021. The search results included cross-sectional, qualitative and quali-quantitative studies. The findings pointed out gaps with regard to the experiences of pharmacists and/or undergraduate pharmacy students on health education for the deaf, eleven articles stand out about pharmaceutical services. The language barrier is a challenge that needs to be overcome, so that the deaf patient can acquire necessary information about the use of medication and health education. We can conclude that there are relevant studies on the offer and promotion of pharmaceutical care for deaf people these being established in different settings.